Biochemical and structural characterization of Penicillium purpurogenum α-D galactosidase: Binding of galactose to an alternative pocket may explain enzyme inhibition. (7th August 2017) - Morales-Quintana, Luis; Faúndez, Carolina; Herrera, Raúl; Zavaleta, Vasni; Ravanal, María Cristina; Eyzaguirre, Jaime; Moya-León, María Alejandra
Abstract: The fungus Penicillium purpurogenum degrades plant cell walls by the action of cellulolytic, xylanolytic and pectinolytic enzymes. The α-D-galactosidase is one of the enzymes which may act on pectin degradation. This enzyme has several biotechnological and medical applications. The aim of this work was to better understand the molecular mechanism of α-D-galactosidase from P. purpurogenum (GALP1). For this purpose, a gene coding for the enzyme was identified from the fungal genome and heterologously expressed in Pichia pastoris . The enzyme belongs to glycosyl hydrolase family 27. The protein of 435 amino acids has an optimum pH and temperature for activity of 5.0 and 50 °C, respectively. The KM for p-nitrophenyl-α-D-galactopyranoside (Galα p NP) is 0.138 mM. The enzyme is inhibited by Galα p NP at concentrations higher than 1 mM, and by the product galactose. A kinetic analysis of product inhibition shows that it is of mixed type, suggesting the presence of an additional binding site in the enzyme. To confirm this hypothesis, a structural model for GALP1 was built by comparative modelling methodology, which was validated and refined by molecular dynamics simulation. The data suggest that galactose may bind to an enzyme alternative pocket promoting structural changes of the active site, thus explaining its inhibitory effect. In silico site-directed mutagenesis experiments highlighted key residues involved in the maintenance of the alternative binding site, and their mutations for Ala predict the formation of proteins which should not be inhibited by galactose. The availability of an α-galactosidase with different kinetic properties to the existent proteins may be of interest for biotechnological applications. Graphical abstract: Highlights: A gene coding for an α-D-galactosidase (GALP1) was identified in P. purpurogenum . The cDNA was expressed in Pichia pastoris and the enzyme characterized. The enzyme is inhibited by excess substrate (Galα p NP) and by the product galactose. GALP1 3D model was built, and an alternative binding pocket for galactose was found. Binding of galactose and other ligands to this alternative site may explain inhibition.